PLANKTON BIOSTRATIGRAPHY AND PALEOCLIMATIC IMPLICATIONS OF AN EARLY LATE MIOCENE SEQUENCE OF LEVKAS ISLAND, IONIAN SEA, GREECE - Antonarakou, A. (Bulletin of the Geological Society of Greece, 2010)
Planktonic foraminiferal biostratigraphy is carried out in an Early Tortonian tectonically active setting, located in the Pre-Apulian Foreland Basin in Levkas Island. The studied section (Manassi section) is composed of hemipelagic silty clays and turbidite sandstones, reflecting sedimentation as a result of thrust activity. The distributional pattern of biostratigraphical significant species suggests that the Manassi section has been deposited during the time interval that Globigerinoides obliquus occurs regularly, the neogloboquadriniids are present in low percentages and Paragloborotalia siakensis is continuously present. The correlation with astronomical tuned sections allowed dating the studied section as ranging between 11.54Ma to 11.2Ma, having a lower Tortonian age, above the Serravallian/Tortonian boundary (Paragloborotalia siakensis planktonic foraminiferal zone). On the basis of the obtained palaeoclimatic curve, a series of palaeoclimatic events are recognized. The faunal composition suggests a cooling trend in the lower part which has been correlated with the Mi5 event. This cooling is followed by a warm-temperate phase, punctuated by several negative peaks in the palaeoclimatic curve. The palaeoclimatic evolution of the study area generally corresponds to the global palaeoclimatic trend with some subtle differences, supporting that the regional climate of this area was not merely controlled by global changes in climate.